(untitled) (Proceedings of the International Conference on Education, 2022)
The career decision of Generation Z, identified as being born between 1995 – 2010, is something to be closely observed as they are becoming the mainstay of the current and future workforce. As Generational Z are more willing to take the risk of job switching, they present one of the greatest challenges for organizations to maintain the turnover rate and cost of replacement. This research is an investigation into the influencing factors for Thai Generation Z concerning their career decision. The survey based on Rich Feller’s Flower was conducted with 556 respondents across different stages of life from secondary school stages, college life stage, and early post-college stage. The survey investigated their demographic information, motivational factors for career decision, and an evaluation part of the 5-Point Likert Scale based on the Rich Feller’s Flower theory. The One-Way ANOVA statistical analysis is used to test research hypotheses whether the motivational factors within the four groups have significantly different means. The results showed that Thai generation Z is influenced by reasonable salary and good welfare, people’s environment in terms of good relationships with coworkers or boss, transferable skills, and knowledge/interests respectively. Based on the hypothesis test, there are statistically significant influencing factors among each different age group. This research provides an insight into the mind of Thai Generation Z concerning their career decision as well as recommendations for organizations to respond to the differing nature of this generation that value passion, work-life balance, people’s friendly environment, and fair salary and good welfare.